Critique of U.S. House Bill 2454 on Climate Change - Michael J. Waggoner (Amsterdam Law Forum, 2010)
The U.S. House of Representatives, in June 2009, approved a bill to create a cap and trade system and a system of regulations and subsidies to address the problems of climate change. The U.S. Senate is now considering remedies for climate change. The approach of House Bill 2454 is ill-advised, and should be rejected by the Senate, because of the problems outlined below. I propose that these problems that would not be presented by a carbon tax, a simpler and more effective remedy for the risk of climate change.